Pengembangan Instrumen Penilaian Portofolio Materi Menulis Teks Eksplanasi - Syahrani, Balqis; Sukenti, Desi (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
This research employs the Research and Development (R&D) method to create and test the effectiveness of a portfolio assessment instrument in writing explanatory texts for 8th-grade students at SMPN 34 Pekanbaru in the academic year 2022/2023. The study focuses on using the ADDIE (Analysis, Design, Development, Implementation, and Evaluations) development model in the process of developing the assessment instrument. The objectives of this research are to evaluate the levels of validity, practicality, and effectiveness of the assessment instrument. The research findings indicate that the developed portfolio assessment instrument meets the validity criteria with a score of 70, making it a valid instrument. Furthermore, it also meets the practicality criteria with an average score of 82.7, indicating that the instrument is highly practical in the teaching context. Moreover, the instrument is proven to be effective with an average score of 78, demonstrating its effectiveness in measuring students' abilities in writing explanatory texts. This research produces a portfolio assessment instrument that can be used in teaching the writing of explanatory texts for 8th-grade students at SMPN 34 Pekanbaru. The instrument is considered valid, practical, and effective in measuring students' writing abilities and can serve as a valuable guide for educators to enhance student writing instruction.